Dihydromyricetin ameliorates liver fibrosis via inhibition of hepatic stellate cells by inducing autophagy and natural killer cell-mediated killing effect - Zhou, Xi (Nutr Metab (Lond), 2021)
BACKGROUND: This study investigated the mechanisms underlying the preventive effect of dihydromyricetin (DHM) against liver fibrosis involving hepatic stellate cells (HSCs) and hepatic natural killer (NK) cells. METHODS: A carbon tetrachloride (CCl(4))-induced liver fibrosis model was established in C57BL/6 mice to study the antifibrotic effect of DHM based on serum biochemical parameters, histological and immunofluorescence stainings, and the expression of several fibrosis-related markers. Based on the immunoregulatory role of DHM, the effect of DHM on NK cell activation ex vivo was evaluated by flow cytometry. Then, we investigated whether DHM-induced autophagy was involved in HSCs inactivation using enzyme-linked immunosorbent assays, transmission electron microscopy, and western blot analysis. Thereafter, the role of DHM in NK cell-mediated killing was studied by in vitro coculture of NK cells and HSCs, with subsequent analysis by flow cytometry. Finally, the mechanism by which DHM regulates NK cells was studied by western blot analysis. RESULTS: DHM ameliorated liver fibrosis in C57BL/6 mice, as characterized by decreased serum alanine transaminase and aspartate transaminase levels, decreased expressions of collagen I alpha 1 (CoL-1α1), collagen I alpha 2 (CoL-1α2), tissue inhibitor of metalloproteinases 1 (TIMP-1), α-smooth muscle actin (α-SMA) and desmin, as well as increased expression of matrix metalloproteinase 1 (MMP1). Interestingly, HSCs activation was significantly inhibited by DHM in vivo and in vitro. As expected, DHM also upregulated autophagy-related indicators in liver from CCl(4)-treated mice. DHM also prevented TGF-β1-induced activation of HSCs in vitro by initiating autophagic flux. In contrast, the autophagy inhibitor 3-methyladenine markedly abolished the antifibrotic effect of DHM. Surprisingly, the frequency of activated intrahepatic NK cells was significantly elevated by DHM ex vivo. Furthermore, DHM enhanced NK cell-mediated killing of HSCs by increasing IFN-γ expression, which was abolished by an anti-IFN-γ neutralizing antibody. Mechanistically, DHM-induced IFN-γ expression was through AhR-NF-κB/STAT3 pathway in NK cells. CONCLUSION: These results demonstrated that DHM can ameliorate the progression of liver fibrosis and inhibition of HSCs activation by inducing autophagy and enhancing NK cell-mediated killing through the AhR-NF-κB/STAT3-IFN-γ signaling pathway, providing new insights into the preventive role of DHM in liver fibrosis. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12986-021-00589-6.